A 2-Stage Surgical Method to Treat Cup-Shaped Ears: The Outer Helix Reconstruction Method. Issue 8 (2nd November 2022) - Sun, Pengfei; Lu, Meng; Luan, Fang; Wang, Yanjin
Abstract : Background: Cup-shaped ear is a common congenital auricle deformity. There are many specific surgical methods, such as V-Y method, Barsky method, Musgrave method, etc., but there is no unified treatment method. The authors used the outer helix reconstruction method for cup-shaped ear and achieved remarkable therapeutic effects. Materials and Methods: The authors performed the outer helix reconstruction on 30 patients with cup-shaped ear. The authors followed up the patients after the stage II operation. The authors used the SPSAU data science analysis platform (https://spssau.com/ ) for statistical analysis of the data. Result: The mean follow-up time was 14.43±4.5 months. The mean preoperative perimeter of auricle was 8.19±0.56 cm. The mean postoperative perimeter of auricle was 10.82±0.49 cm. The mean perimeter of the healthy auricle was 10.89±0.44 cm. Through data analysis, the authors found that the comparison between preoperative and postoperative auricle perimeters was statistically significant ( P <0.05). The comparison between postoperative auricle perimeter and the perimeter of the healthy auricle was not statistically significant ( P >0.05). In terms of postoperative satisfaction of patients and their families, the satisfaction rate was 100%. In terms of postoperative complications, there were 1 case of incision dehiscence, 0 cases of incision infection, 2 cases of incision hematoma, and 0 cases of postoperative skin flap ischemia and necrosis. Conclusion: The outer helix reconstruction method is suitable for most cup-shaped ears, and the operation is simple and the effect is remarkable. It is worthy of promotion and application in plastic surgery clinical.